Casque d'or [videorecording (DVD)] - Becker, Jacques, 1906-1960; Becker, Jacques, 1906-1960; Signoret, Simone, 1921-1985; Signoret, Simone, 1921-1985; Reggiani, Serge; Reggiani, Serge; Dauphin, Claude, 1903-1978; Bussières, Raymond, 1907-1982; Modot, Gaston, 1887-1970 (Criterion collection, 2005)
In an open-air dance hall, the members of Leca's gang are relaxing with their ladies. One of the ladies, Marie, meets Manda, who is a carpenter by trade. Marie's man Roland is a jealous sort and does not like the idea of Marie and Manda becoming friendly, and Leca himself has his eye on Marie. What follows is a story of love, death, friendship and jealousy during the Belle Epoque.